Development projects observed - Hirschman, Albert O. (Washington : The Brookings Institution, 1967)
This is a study of selected capital assistance projects financed by the World Bank. This is in the wake of two decades of sustained efforts to promote growth and change in the low-income countries presents a rich field for scholarly inquiry and new insights into the development process.
Includes bibliographical footnotes and index.
lje 16/10/2018
Loans
Keywords: Economic development projects